T cells targeting NY-ESO-1 demonstrate efficacy against disseminated neuroblastoma. (2nd January 2016) - Singh, Nathan; Kulikovskaya, Irina; Barrett, David M.; Binder-Scholl, Gwendolyn; Jakobsen, Bent; Martinez, Daniel; Pawel, Bruce; June, Carl H.; Kalos, Michael D.; Grupp, Stephan A.
Abstract: The cancer-testis antigen NY-ESO-1 is expressed by many solid tumors and has limited expression by mature somatic tissues, making it a highly attractive target for tumor immunotherapy. Targeting NY-ESO-1 using engineered T cells has demonstrated clinical efficacy in the treatment of some adult tumors. Neuroblastoma is a significant cause of cancer mortality in children, and is a tumor type shown to be responsive to immunotherapies. We evaluated a large panel of primarily resected neuroblastoma samples and demonstrated that 23% express NY-ESO-1. After confirming antigen-specific activity of T cells genetically engineered to express an NY-ESO-1 directed high-affinity transgenic T cell receptor in vitro, we performed xenograft mouse studies assessing the efficacy of NY-ESO-1-targeted T cells in both localized and disseminated models of neuroblastoma. Disease responses were monitored by tumor volume measurement and in vivo bioluminescence. After delivery of NY-ESO-1 transgenic TCR T cells, we observed significant delay of tumor progression in mice bearing localized and disseminated neuroblastoma, as well as enhanced animal survival. These data demonstrate that NY-ESO-1 is an antigen target in neuroblastoma and that targeted T cells represent a potential therapeutic option for patients with neuroblastoma.